2006
DOI: 10.1097/01.ccm.0000203947.60552.dd
|View full text |Cite
|
Sign up to set email alerts
|

Weekend and weeknight admissions have the same outcome of weekday admissions to an intensive care unit with onsite intensivist coverage*

Abstract: In an intensive care unit staffed by onsite certified intensivists 24 hrs/7 days, we found no compromise in the care of patients admitted during weekends and weeknights. These findings suggest that such coverage helps in ensuring consistency of care and therefore represents a potentially improved model for intensive care unit practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
122
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(137 citation statements)
references
References 32 publications
11
122
4
Order By: Relevance
“…Thus, the admission by day of the week may be less likely to infl uence outcomes in critical care settings, a hypothesis that is supported by prior investigations. [21][22][23] Our study can be compared with prior investigations by Aujesky et al 12 and Bell and Redelmeier. 13 Aujesky et al 12 showed an adjusted OR of 1.17 (95% CI, 1.03-1.34) for mortality from PE on the weekend in a Pennsylvania health-care database from 2000 to 2002.…”
Section: Discussionmentioning
confidence: 49%
“…Thus, the admission by day of the week may be less likely to infl uence outcomes in critical care settings, a hypothesis that is supported by prior investigations. [21][22][23] Our study can be compared with prior investigations by Aujesky et al 12 and Bell and Redelmeier. 13 Aujesky et al 12 showed an adjusted OR of 1.17 (95% CI, 1.03-1.34) for mortality from PE on the weekend in a Pennsylvania health-care database from 2000 to 2002.…”
Section: Discussionmentioning
confidence: 49%
“…Once a medical hypothesis, the concept of the "weekend effect" has become increasingly examined in the medical literature. 5,7,8,[13][14][15][16][17][18][19] Arguably the most substantial study investigating at the "weekend effect" is the work of Bell and Redelmeier published in 2001. 7 They looked at approximately 3.8 million acute care hospital admissions in Ontario, Canada, over a 10-year period.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, studies that have evaluated round-the-clock 24/7 ICU and trauma staffing found no variability between arrival time and outcomes of care. 11,12 In a recent study of a general medicine service that maintains the same staffing ratio on weekends as that on weekdays, researchers found that night or weekend admission was not associated with worse patient outcomes and suggested that consistent staffing, coordinated handoffs, and rotation schedules that protected against discontinuity may facilitate narrowing the gap in disparity. 13 Moreover, in a study that evaluated policies to improve communication in surgical care, including resident-attending notification regarding routine weekend patient status and weekend patient visits by an attending, results showed significant reductions in potentially harmful communication breakdowns.…”
Section: Innovative Solutionsmentioning
confidence: 99%